Ação de Sais de Cobre sobre a Xantina Desidrogenase na Carcinogênese Hepática de Ratas - Affonso, Ottilia R. (2023)
Blood serum xanthine dehydrogenase activity was inhibited by cupric acetate (CuAc) (12,5 mg/100 g body weight). The study of the inhibition by CuAc was related with the hepatic changes produced by D-L-ethionine (12,5 mg/100 g body weight). "In vitro" experiments showed that CuAc is a potent inhibitor of the xanthine dehydrogenase activity and that this inhibition is of a non-competitive type. Ehtionine protects against the inhibitory effect of CuAc, both "m vivo" as "in vitro", probably by the formation of a copper complex. Experiments with O2 as eléctron acceptor seemed to indicate that the cupric sait competes "m vitro" with the reduction of the triphenyltetrazolium chloride in the electron transfer reaction.